ETHICAL ANALYSIS OF ISLAMIC COMMUNICATION ON STAND-UP COMEDY SAMARINDA - Sri Ayu Rayhaniah; Ardina Ardiana; Sy. Nurul Syobah (Universitas Islam Negeri (UIN) Mataram, 2022)
Stand-up comedy is one of the arts that are in great demand by various circles because of its entertaining nature. However, the delivery of stand-up comedy material and improper wording sometimes trigger audience confusion. This makes comic or stand-up comedy actors many who reap protests. Thus the ethics of Islamic communication are indispensable in stand-up comedy. Starting from the search for materials and writing materials, then adjusted to existing places and norms, to the delivery of materials on stage. To find out this, researchers conducted field research aimed at knowing the application of Islamic communication ethics in Samarinda stand-up comedy. Research is carried out using qualitative methods. Selection of informants as data sources based on purposive sampling by predetermined criteria. Data collection is done by observation, interviews, and documentation. Data analysis is carried out in conjunction with the data collection process using data analysis techniques that include data condensation, data presentation, and conclusion drawing to obtain research results. The results of this study found that there is an application of Islamic communication ethics in Samarinda stand-up comedy. This can be seen from the search for writing material, the adjustment of the material to the stage they polled before performing, to the delivery of the material on the stage. The ethics of Islamic communication in stand-up comedy are: qaulan sadidan, qaulan layyina, qaulan ma'rufa, qaulan maysura, qaulan karima and qaulan baligha.